HUBUNGAN FREKUENSI PEMBERIAN ASI DENGAN KEJADIAN IKTERUS PADA BBL 2-10 HARI DI BPM N PADANG PANJANG TAHUN 2016 - Husna, Novriani (Jurnal Kesehatan - STIKes Prima Nusantara, 2017)
Early marriage is a phenomenon that often occurs in developing countries such as in South Asia, Southeast Asia, Africa, and Latin America. Early marriage in Indonesia ranks second most after Cambodia. The Indonesian Ministry of Health (2016) reports that around 25% of Indonesians are married at an early age or below the ideal age recommended by the government, which is 21 years for women and 25 years for men. This research is quantitative research with a cross-sectional design or approach. The purpose of the study was to find out the relationship between free and cultural relationships with the incidence of early marriage in the District of Pasie Laweh, Lubuk Alung Subdistrict, which was carried out on date 2 February 2017 to 12 March 2017 with a population of 35 mothers, a sample of 35 respondents, a total sampling technique. The statistical test used is chi-square. The results of the study were a relationship of free association with the incidence of early marriage in Pasie Laweh Subdistrict, Lubuk Alung Subdistrict, in 2017 (p-value = 0.003). There is a cultural relationship with the incidence of early marriage in Pasie Laweh Village, Lubuk Alung Sub-district in 2017 (p-value = 0.022). It is expected that all adolescents of Pasie Laweh Village to get along well, fill their days with positive and productive activities, for example, learning, forming a youth mosque organization in their place of residence. So this is what will be the capital and protection for youth to avoid negative actions